Examining Stevenson’s conceptualisation of entrepreneurship as opportunity-based firm behaviour - Abdul Majid, Izaidin; Dora, Mohd Taib; Ismail , Kamariah (2008)
Increasingly, one of the field’s most popular conceptualisations of entrepreneurship is Stevenson’s (1983), which views entrepreneurship as a management approach of pursuing opportunity without regards to resources currently controlled. This paper shows how the operationalisation of this approach is replicated in the Malaysian business context. The analysis employed here is the exploratory factor analysis and Cronbach’s Alpha test on the data set. The results showed that it was possible to identify five sub-dimensions of the opportunity-based firm behaviour construct with high discriminant validity and moderate to high reliabity, which represent dimensions of Stevenson’s theoretical reasoning. Following Brown et al’s (2001) approach, we label these sub-dimensions as Strategic Orientation, Resource Orientation, Management Structure, Growth Orientation and Entrepreneurial Culture.